Influence Of Treated Recycled Aggregates As Partial Aggregate Replacement On Properties Of Concrete - Ching, Meng Xuan (Universiti Sains Malaysia, 2021)
Rapid growth of the construction industry generates a huge amount of construction and demolition waste causing an irreparable damage to the environment. Therefore, application of waste materials as recycled aggregate (RA) in concrete is an efficient and economical method to address the issue. However, recycled aggregate concrete (RAC) has lower performance compared to natural aggregate concrete (NAC). Hence, treatment on the RA is required to improve the properties of the RA and of the resulting concrete. In this study, two objectives were investigated; (a) efficiency of different treatment method of RA based on properties of concrete, (b) the optimum replacement ratio of acid treated RA in concrete. The RA used in this study was crushed concrete cubes from the MDC Batu Kawan concrete batching plant. The RA was treated using cement slurry wrapping method and acetic acid treatment method. Seven concrete mixes were prepared and tested based on workability, density, compressive strength, flexural strength and splitting tensile strength. Comparative study of treatment method was done at a 20% replacement ratio of treated RA. Whereas prediction of optimum replacement ratio of acid treated RAC was examined based on the properties of concrete. The results revealed that cement slurry treated RAC has greater mechanical properties compared to the acetic acid treated RAC and untreated RAC. Furthermore, it was found that the mechanical properties of acid treated RAC improves as the replacement ratio of RA increases. The optimum replacement ratio of acid treated recycled aggregate was determined to be at 30%. However, all treated RAC exhibit a reduction range from 13.75% to 68.75% in workability of the fresh concrete.